Bidragsydere 21 - Christiansen, Inge; Dahl, Camilla Luise; Glienke, Laila; Horn, Anne Stubbe; Klose, Susanne; Rykind-Eriksen, Kirsten; Emiland, Kirsten; Kragelund, Minna; Nygaard, Agnethe; Olsen, Wini Maj Bjørneboe; Rasmussen, Inger (Dragtjournalen, 2024)
Bidragsydere til Dragtjournalen nr. 21 Contributor for Dragtjournalen nr. 21